First cut [large type] - Melinek, Judy; Mitchell, T. J. (Melinek, Judy. Dr. Jessie Teska novel, 2020)
For San Francisco's newest medical examiner, Dr Jessie Teska, it was supposed to be a fresh start. A new job in a new city. A way to escape her own dark past. Instead she faces a chilling discovery when a suspected overdose case contains hints of something more sinister. Jessie's superiors urge her to close the case, but as more bodies land on her autopsy table, she uncovers a constellation of deaths that point to an elaborate plot involving nefarious opioid traffickers and flashy tech titans who got rich off Bitcoin. Autopsy means 'see for yourself, ' and Jessie Teska won't stop until she has seen it all - even if it means the next corpse on the table could be her own.